1995
DOI: 10.1161/01.str.26.1.74
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral Autoregulation Dynamics in Premature Newborns

Abstract: Computerized coherent averaging of the cerebral blood flow velocity response to spontaneous blood pressure transients offers a promising new method for noninvasive bedside assessment of autoregulation in patients undergoing intensive care. The time course for autoregulation, when present, is in agreement with that reported in adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
68
1
4

Year Published

2001
2001
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(76 citation statements)
references
References 21 publications
3
68
1
4
Order By: Relevance
“…An explanation for this aberrant result could neither be found during that experiment nor at postmortem autopsy, but as autoregulatory patterns, although slightly impaired in two animals, were found in the seven other animals, we conclude that this experimental model enables repeated valid assessments of cerebrovascular autoregulation. Even including this nonautoregulating animal the values of mean static autoregulatory response was well below the proposed thresholds of impaired autoregulation of 0.5 and 1.5% changes in CBF per mmHg change in MAP previously reported to indicate impaired cerebrovascular autoregulation in humans (18,19).…”
Section: Effects On Cerebrovascular Autoregulationcontrasting
confidence: 62%
“…An explanation for this aberrant result could neither be found during that experiment nor at postmortem autopsy, but as autoregulatory patterns, although slightly impaired in two animals, were found in the seven other animals, we conclude that this experimental model enables repeated valid assessments of cerebrovascular autoregulation. Even including this nonautoregulating animal the values of mean static autoregulatory response was well below the proposed thresholds of impaired autoregulation of 0.5 and 1.5% changes in CBF per mmHg change in MAP previously reported to indicate impaired cerebrovascular autoregulation in humans (18,19).…”
Section: Effects On Cerebrovascular Autoregulationcontrasting
confidence: 62%
“…Birth stress may have abolished cerebral autoregulation during hemorrhagic hypotension in the 127-d lambs in our study. This observation is supported by the observed failure of cerebral autoregulation in some studies in preterm-born humans (36,37). However, Tsuji et al (38) showed evidence of impaired autoregulation only in a subgroup of preterm infants who are at risk for developing germinal matrix-intraventricular hemorrhage and periventricular leukomalacia, whereas Tuszczuk et al (39) Brain cell function was preserved at MABP levels below the threshold value for maintenance of Qcar in the 141-d lambs.…”
Section: Discussionmentioning
confidence: 89%
“…Others have attempted to determine the status of cerebral autoregulation in premature infants by examining the slope (percentage change in CBF/1 mm Hg change in MABP) of the relationship between measurements of CBF and MABP (14,30,31). In addition to arbitrarily defining a critical value between 0.5 and 1.5% change in mCBFv/1 mm Hg change in MABP as intact autoregulation (30 -32), they did not take into account simultaneous changes in PaCO 2 that clearly cause changes in CBF and MABP in the same direction, which may be interpreted as impaired autoregulation.…”
Section: Discussionmentioning
confidence: 99%